Hubungan Indeks Massa Tubuh dan Aktivitas Fisik Terhadap Daya Tahan Kardiovaskular Pada Mahasiswa Fakultas Kedokteran Universitas Abulyatama - Ghafur, Baldhan; Candra, Aditya; Andrianty, Syarifah Nora (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Obesity is a global problem that affects approximately 2 billion people worldwide and has the potential to jeopardize public health. In Indonesia, over a 10-year period there has been a significant increase in obesity, from 10.5% in 2007 to 21.8% in 2018. The study aims to determine the relationship between body mass index and physical activity on cardiovascular endurance in Abulyatama University Faculty of Medicine Students. This study used a descriptive method with an Analytical Observational approach. The population of this study were all students of the Abulyatama University Medical Education Study Program. The sample used in this study were 30 students using the Totally Sampling Technique. The results of this study indicate that there are 30 valid and reliable. The test results using the chi-square test explain that the variables of body mass index and physical activity have a significant relationship, because these variables have a significance value <0.05 The respondent's characteristic data includes gender and age. Based on the results obtained, it can be concluded that the Relationship between Body Mass Index and Physical Activity to Cardiovascular Endurance explains that the variables of body mass index and physical activity there is a significant relationship between these variables.